“Abbiamo detto con te no che tu hai ta da di da dim (Moves Right Hand on the Beat)”—The Interplay of Semiotic Modes in Chamber Music Lessons Under a Multimodal and Interactional Perspective - Messner, Monika (Frontiers in Communication, 2022)
This paper analyzes the interplay of semiotic modes employed by a teacher and music students in a chamber music lesson for instructing, learning and discussing. In particular, it describes how specific higher-level actions are accomplished through the mutual contextualization of talk and further audible and visible semiotic resources, such as gesture, gaze, material objects, vocalizing and music. The focus lies on modal complexity, i.e. how different modes cohere to build an action and on modal intensity, i.e. the importance of specific modes related to their useful modal reaches. The study also attends to the linking and coherent coordination of interactional turns by the participants to achieve mutual understanding about musical ideas and concepts. The rich multimodal texture of instructional, negotiation and discussion actions in chamber music lessons stresses the role of multimodality and multimodal coherence for investigating music and pedagogy from an interactional perspective.